Marine Renewable Energy - Rusu, Eugen; Belibassakis, Kostas; Lavidas, George (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The topic "Marine Renewable Energy" brings together four MDPI journals, Energies, Journal of Marine Science and Engineering, Inventions, and Processes, with 51 papers published. The present reprint includes a selection of 26 significant scientific works structured into three main subjects: S1 - wind turbines, including both fix and floating structures (7); S2 - developments in ocean energy and emerging floating photovoltaic systems (10); and S3 - economic assessments related to offshore renewable energy extraction (9). The present reprint seeks to contribute to the renewable energy agenda through enhanced scientific and multi-disciplinary works, aiming to improve knowledge and performance in harvesting offshore renewable energy.